Comparative Degradation of LDPE, HDPE and HMHDPE under Different Soil Conditions - Konduri, Mohan K.R.; Bogolu, Venkata Reddy (Journal of Research Updates in Polymer Science, 2014)
The Present work includes, degradation of polyethylene under different environmental conditions to know the effect of physical, chemical and biological factors prevailing in those conditions on degradation of polyethylene. Plastic films viz., Low density polyethylene (LDPE), High density polyethylene (HDPE) and High molecular weight high density polyethylene (HMHDPE) each were incubated in three different conditions viz., black soil, sandy soil and red soil for a period of 3 months. The changes in the properties of plastic films after incubation was studied by change in the weight of the plastic film and mechanical parameters like tensile strength, breaking load and percentage of elongation. Among all the plastic films HDPE was found to be highly susceptible with 33% weight loss and 40% reduction in percentage of elongation compared to LDPE with 26% weight loss and 34 % reduction in percentage of elongation in black soil. Whereas HMHDPE found to be highly resistant in all the soils with no significant weight loss and percentage of elongation (15%). None of the plastic films had shown degradation in sandy soil even after incubation for 3 months. FTIR spectroscopy results showed that HDPE film incubated in black soil had undergone extensive degradation when compared with un incubated HDPE film.